Risk of SARS-CoV-2 transmission in the close contacts in a small rural area in the Veneto Region (NE-Italy): past evidence for future scenarios - Bassanello, Marco; Geppini, Ruggero; Bonsembiante, Erminio; Coli, Ugo; Farencena, Aldo; D’Aquino, Maurizio; Gambaro, Andrea; Buja, Alessandra; Baldovin, Tatjana (Frontiers in Public Health, 2023)
Background During the first pandemic phase of COVID-19, an epidemiological study, named First survey, was conducted on the population of a small rural area in northern Italy. In spring 2020, the results showed how a prolonged lockdown slowed down the spread of the virus. Methods After contacting positive First Survey subjects and their families, those who decided to join voluntarily underwent a blood test to assess the presence of qualitative lgG about two months after the previous one. This was to determine if IgG persisted in individuals who tested positive in the First Survey as well as to assess the antibody status of their close family members, to determine if they were unintentionally infected. Results Based on serological analysis, 35.1% of the samples contained blood IgG. In subjects who tested positive during the First Survey, 62.5% remained IgG positive more than two months later. Among family members who were exposed to a positive relative, 23.7% were infected. Linear regression analysis showed that the presence of an infected person within a household resulted in the infection spreading to the others, but not excessively. Induced isolation extinguished the infection regardless of the extent of the contagion (intra-family or extra-family). Micro-outbreaks of Sars-Cov-2 infection which arose in the same household from extra-familial infections played a decisive role on the statistical significance of IgG-positive subjects (p<0.001). Discussion The study reveal 52.6% of the IgG-positive subjects in the Second Survey came from the First Survey and 47.4% were family members previously in contact with positive subjects. Data suggest that there have been undiagnosed patients feeding the spread of the virus since the beginning of the pandemic. In conclusion, for future pandemics, it will be necessary: i) to ensure the rapid isolation of symptomatic patients and the early identification of their close contacts; ii) to carry out the maximum number of tests in the shortest possible time, both on symptomatic and asymptomatic subjects; iii) to implement information campaigns to make people aware of their risks, and implement clear, non-conflicting communication.